2015
DOI: 10.1007/s12020-015-0594-x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of the truncated isoform of somatostatin receptor subtype 5 associates with aggressiveness in medullary thyroid carcinoma cells

Abstract: The truncated somatostatin receptor variant sst5TMD4 associates with increased invasiveness and aggressiveness in breast cancer. We previously found that sst5 activation may counteract sst2 selective agonist effects in a medullary thyroid carcinoma (MTC) cell line, the TT cells, and that sst5TMD4 is overexpressed in poorly differentiated thyroid cancers. The purpose of this study is to evaluate sst5TMD4 expression in a series of human MTC and to explore the functional role of sst5TMD4 in TT cells. We evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…In PCa, ssts are expressed and are capable of mediating such functions (5); however, some initial but limited studies that used SSAs reported no benefit in overall survival in patients with PCa (11,26), and the mechanistic reasons of this clinical failure are still unknown. Given that aberrant alternative splicing is a cancer hallmark (13,27) and our group has demonstrated the presence and relevant pathologic function of the spliced sst5TMD4 variant in other cancer types (15,(17)(18)(19)(20), we hypothesized that sst5TMD4 could be present and play a role in the development and/or progression of PCa or in the response to SSAs in PCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PCa, ssts are expressed and are capable of mediating such functions (5); however, some initial but limited studies that used SSAs reported no benefit in overall survival in patients with PCa (11,26), and the mechanistic reasons of this clinical failure are still unknown. Given that aberrant alternative splicing is a cancer hallmark (13,27) and our group has demonstrated the presence and relevant pathologic function of the spliced sst5TMD4 variant in other cancer types (15,(17)(18)(19)(20), we hypothesized that sst5TMD4 could be present and play a role in the development and/or progression of PCa or in the response to SSAs in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in contrast to the predominant plasma membrane localization of other ssts, sst5TMD4 demonstrates a preferential intracellular localization wherein it may disrupt the function of other ssts, mainly sst2 and sst5 (14). Of more interest, sst5TMD4 is barely expressed in normal tissues but is highly overexpressed in several tumors and cancers, including pituitary adenomas (15,16), breast cancer (17), thyroid carcinoma (18,19), and NETs (20), where it correlates with aggressive clinical parameters and promotes cell proliferation, migration, invasion, and hormone secretion (15,17,19,20). Indeed, sst5TMD4 expression is negatively correlated with the ability of SSAs to reduce growth hormone secretion in pituitary adenomas (16) and inhibits the ability of sst2-transfected cells to respond to SST and/or SSAs (17).…”
mentioning
confidence: 99%
“…Moreover, since antisecretory and antiproliferative effects occur at different time-windows, involvement of different receptors and/or molecular mechanisms has been also proposed [ 17 ]. For instance, the presence of the truncated variant sst5TMD4, which interacts with sst2 and disrupts its signaling [ 18 ], may influence spontaneous or SSA-inhibited hormone secretion [ 19 ], as well as aberrant cell proliferation [ 18 , 20 ], and has been proposed as a biomarker for increased risk of malignant behavior in certain tumors [ 18 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…PTs retain SSTR and DR expression, whose activation elicits different effects, depending on the specific pituitary cell type (11). sst5TMD4, on the other hand, has been found to be rarely expressed in normal tissues, whilst it is overexpressed in PT, breast and thyroid cancer (12,13,14). Thus, presumably, targeted pharmacological treatments may be developed, allowing control of tumour cell metabolism.…”
Section: Somatostatin and Drs In Ptsmentioning
confidence: 99%
“…SSTR5 is the predominant subtype in normal human pituitary, followed by SSTR2, SSTR1, SSTR3 and SSTR4. Canonical SSTRs are heterogeneously expressed in PT, whereas the sst5TMD4 splice variant has been found to be overexpressed in PT, breast and thyroid cancer (12,13,14). Several studies focused on SSTR characterization with the use of different techniques, from qPCR (11,28,29,30) to IHC (31,32,33) and in vivo scintigraphy (31,34,35).…”
Section: For: the Case For Pituitary Receptor Profilingmentioning
confidence: 99%